PENGGUNAAN MEDIA INTERAKTIF TERHADAP MOTIVASI BELAJAR SISWA - Khoirun Nisa'; Linda Dwi Aryanti (Hijri, 2023)
This article discusses the use of interactive media in increasing student motivation. The article provides a brief overview of the benefits of using interactive media in education, such as increasing student engagement and adapting to individual learning styles. This article also highlights some of the disadvantages of using interactive media, such as the potential for distraction and the cost of developing interactive media. This article concludes that while interactive media can be an effective tool in increasing student motivation, it is important for educators to carefully consider their use and ensure that they are used in a way that maximizes their benefits while minimizing their drawbacks.Interactive Media, Learning Motivation, Students, Learning Experience